Within‐person coupling of changes in cortisol, testosterone, and DHEA across the day in adolescents. Issue 6 (26th October 2013) - Marceau, Kristine; Ruttle, Paula L.; Shirtcliff, Elizabeth A.; Hastings, Paul D.; Klimes‐Dougan, Bonnie; Zahn‐Waxler, Carolyn; Shirtcliff, Elizabeth A.
Abstract We comprehensively examined within‐person and between‐person associations between cortisol and DHEA and cortisol and testosterone across the day. Data are from a sample of 213 adolescents aged 11–16 (M = 13.7, SD = 1.5 years) from the Northeastern US who were oversampled for psychopathology symptoms. Six repeated measures of hormone levels across 3 days were used to test three specific questions of cortisol‐DHEA and cortisol‐testosterone associations within individuals (coupling) across the day, and one question of cortisol‐DHEA and cortisol‐testosterone diurnal slopes were associated between adolescents. Results consistently revealed positive cortisol‐DHEA and cortisol‐testosterone coupling across the day, often more pronounced in girls relative to boys. Cortisol and DHEA slopes were positively associated, whereas cortisol and testosterone were negatively associated between‐adolescents. Findings suggest multiple mechanisms and highlight the multifaceted nature of associations of hormone changes during adolescence and importance of considering both axes for between‐ and within‐person aspects of neuroendocrine development. © 2013 Wiley Periodicals, Inc. Dev Psychobiol 57: 654–669, 2015.